PENGARUH CITRA DESTINASI DAN NILAI PELANGGAN TERHADAP KEPUTUSAN BERKUNJUNG DI PULAU BOKORI - Sugiale, Eko Putra; Rommy, Nursaban; Isalman, Isalman (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo)
This study aims to determine the effect of destination image and customer value on the decision to visit Bokori Island. This type of research uses quantitative research. The population in this study were those who had visited Bokori Island. The sample in this study amounted to 88 respondents. The sampling technique in this study was to use Accidental Sampling. The method of data collection in this research is to use questionnaires and documentation. This study uses multiple linear regression analysis. The results of this study indicate that: (1) simultaneously destination image and customer value have a positive and significant effect on visiting decisions (2) partially destination image variables have a positive and significant effect on visiting decisions. (3) partially the customer value variable has a positive and significant effect on visiting decisions.